2011
DOI: 10.1016/j.sdentj.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate specialties interest, career choices and qualifications earned by male dentists graduated from King Saud University

Abstract: Most of the dental graduates were motivated and eager to continue their postgraduate education to get either clinical specialty or academic degrees from nationally and internationally well recognized and known Universities and programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 8 publications
1
19
0
1
Order By: Relevance
“…The majority of male respondents in this study preferred oral and maxillofacial surgery, followed by orthodontics, as their postgraduate specialties of interest, which is partially in accordance with the results of a previous Saudi study in which the majority of male dentists preferred the specialties of prosthodontics and orthodontics [10]. Furthermore, the majority of female subjects preferred operative dentistry, followed by pediatric dentistry, which is in contrast to a previous Saudi study reporting that the majority of female dentists preferred orthodontics, followed by endodontics [11].…”
Section: Discussionsupporting
confidence: 91%
“…The majority of male respondents in this study preferred oral and maxillofacial surgery, followed by orthodontics, as their postgraduate specialties of interest, which is partially in accordance with the results of a previous Saudi study in which the majority of male dentists preferred the specialties of prosthodontics and orthodontics [10]. Furthermore, the majority of female subjects preferred operative dentistry, followed by pediatric dentistry, which is in contrast to a previous Saudi study reporting that the majority of female dentists preferred orthodontics, followed by endodontics [11].…”
Section: Discussionsupporting
confidence: 91%
“…In the study conducted at Prince Sattam Bin Abdulaziz University Dental College, job satisfaction was an important factor in selecting orthodontics as the future specialty of choice among students. Similarly, three previous studies[ 9 10 11 ] conducted among orthodontic residents in USA, UK, and Saudi Arabia had shown that job satisfaction was the most common reason for selecting the specialty of orthodontics. At the Prince Sattam Bin Abdulaziz University Dental College, 7 out of the 27 students (26%) who had taken part in the study felt that this branch of dentistry was intellectually challenging, thus giving a higher response rate when compared to the rate reported in a previous study (18.21%) conducted by Noble et al .…”
Section: Discussionmentioning
confidence: 76%
“…Advancing the quality of clinical skills as well as the research output will drive the medical and dental care forward by improving the service level, patient satisfaction, and reducing the complication rate[ 6 8 ] Nowadays, the number of dental graduates in Saudi Arabia is exceeding 2500 from over 30 dental schools every year. [ 9 10 ] Orthodontics has gained immense popularity as a postgraduate dental specialty program in Saudi Arabia. [ 11 ] Recognizing the motivation of dental students in choosing orthodontics as a career specialty might provide valuable information pertaining to the general perception among graduates about this specialty.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Saudi female dental graduates of King Saud University conducted between 1984 and 2006, 54% were found to have continued their postgraduate education, 25 a similar study was also conducted in Saudi male graduates between 1982 and 2004 and showed that 77% of the male graduates finished postgraduate dental educations. 26 …”
Section: Discussionmentioning
confidence: 99%